СРАВНИТЕЛЬНАЯ ХАРАКТЕРИСТИКА РУССКОГО И КАРАКАЛПАКСКОГО НЕОБРЯДОВОГО ЛИРИЧЕСКОГО ФОЛЬКЛОРА - Алламуратова, Г.Ж.; Алламуратова, А.Ж. (SCIENCE and SOCIETY, 2024)
The article examines the features of Russian and Karakalpak folk non-ritual poetry, identifying similarities and differences in the themes and images of folk songs of the Russian and Karakalpak peoples.
Keywords: folklore; non-ritual lyrics; lyric song; images; specifics